An argyrodite sulfide-based superionic conductor synthesized by a liquid-phase technique with tetrahydrofuran and ethanol. Issue 2 (12th December 2018) - Yubuchi, So; Uematsu, Miwa; Hotehama, Chie; Sakuda, Atsushi; Hayashi, Akitoshi; Tatsumisago, Masahiro
Abstract : An argyrodite Li6 PS5 Br electrolyte is synthesized using tetrahydrofuran and ethanol solvents and shows the highest conductivity of 3.1 mS cm −1 . Abstract : Sulfide-based solid electrolytes with halide elements are essential components of advanced all-solid-state batteries. Argyrodite crystals are viable candidates as solid electrolytes for realizing all-solid-state batteries. However, a simple and effective route for the synthesis of these solid electrolytes is required. Herein, argyrodite Li6 PS5 Br superionic conductors were synthesized from a homogeneous solution by a liquid-phase technique. The Li6 PS5 Br solid electrolyte was prepared in a shorter synthesis time of one day using tetrahydrofuran and ethanol as compared with the solid-phase method. More importantly, of all the sulfide-based solid electrolytes prepared by liquid-phase techniques, Li6 PS5 Br showed the highest ionic conductivity of 3.1 mS cm −1 at 25 °C. The obtained particle size of 1 μm is suitable for application in all-solid-state cells. Moreover, coating electrode active materials with the solid electrolyte using the precursor solution led to a large contact area between the electrode and electrolyte and improved the cell performance. In addition, infiltrating a porous electrode with the precursor solution of the solid electrolyte is suitable for forming homogeneous composite electrodes to improve the cell performance. The all-solid-state cell using the Li6 PS5 Br fine powder with a high conductivity of 1 mS cm −1 or more exhibited a reversible capacity of 150 mA h g −1 . This technique is effective for the industrial production of solid electrolytes and is applicable to all-solid-state batteries.